PERBEDAAIN HASIL PENGUKURAN HEMATOKRIT METODE MIKRO PADA DARAH YANG MENGGUNAKAN ANTIKOAGULAN EDTA 10 UL DAN 50 UL PADA KONSENTRASI IO % - Budi Santosa; Waenah . . (JURNAL LITBANG, 2005)
The anticoagulant that is usually used in hematology checking (especially micro hematokrit) is EDTA (Enthylen diamine Tetra Asetat). There are two form of this anticoagulant, they are solid / dry and liquid / condensation. Usage of EDTA has to according to the rule. It is mg/l m l liquid EDTA If usage anticoagulant EDTA More than the rule the blood will be frost and if more to erythrocyte it will dwindle, so influences of the down of hamatolvit value. This research is done to know how far the differences of micro hematolrit measurement result to the blood by using EDTA Volume I0 ul and 5 ul in concentration 10%  This research is done in Marc 2005. The research type that is done is descriptive, The research population is the students at level III of Analis Kesehatan Muhammadiyah Semarang. The sample is 41 Students that is taken in random. From the blood sample research result that is use anticoagulant EDTA I0 ul is got average 37, 78 and blood sample that is use anticoagulant EDTA 50 ul is got average 34,65. This evidence show that the usage of anticoagulant EDM volume 50 ul in micro hernatolcrit checking is going Down if compare to volume 10 ul. By using t test statistical is got t count 5,322 bigger than t table 2,021 with error level 5% And get the conclusion; there is meaning differences between adding anticoagulant EDTA volume I 0 ul and 5 0 ul with concentration I 0 % Keyword: hematokrit